On The Performance Of The Motorcycle Engine Using Used Lubricant Oil - Jamil, Saiful Syazwan Shamsul (Universiti Sains Malaysia, 2017)
Due to the rapid need in automotive industries, the production of lubricant oil is so abundant in the market, Manufacturers seek different technologies such as additives and blend. Due to highly competitive market, this however, increases the price of engine oil keep arising as many manufacturer competing to sell their product. The cost of vehicle maintenance thus become a burden to the users. Users then try to discover methods in order to reduce the maintenance cost of their vehicle. In this study, the engine oil that has been used for several mileage will be reused in order to study the effect on the engine performance, particularly the torque and power of the engine. The effect will be analysed whether it is practically safe or not to reused the oil to lubricate the engine. The engine was run using different types of used oil at Wide Open Throttle (WOT). The performance graph will be compared with base engine oil. Result showed that there were slight drop in performance which are the torque is in the range of around 0.1 - 3.58 % whereas the horsepower is in the range between 0.01 - 3.8 %. This is due to drop in effectiveness of the used engine oil. The composition of the used engine oil may also affect the performance drop. This is because the operating condition of the engine has accumulated with carbon deposit, which consequently affect the efficiency too. However, in the economical aspect, this method could benefit many vehicle user in order for them to reduce their maintenance cost. Based on few sample of calculation Users could save up to 50% of their maintenance cost using reused oil or by extending the mileage interval service.